Comparing and contrasting the evolution through time of organizational sustainability initiatives. Issue 3 (6th September 2018) - Rodriguez, Rocio; Svensson, Göran; Eriksson, David
Abstract : Purpose: The purpose of this study is to compare private and public hospitals' sustainability actions, as well as to contrast their organizational evolution over time (i.e. past, present and expected future) in the Spanish health-care sector. Sustainability initiatives refer to organizations' economic, social and environmental actions. Design/methodology/approach: This study applies an inductive approach based on judgmental sampling and in-depth interviews of key informants at private and public hospitals in the Spanish health-care sector. Data were gathered from the executive in charge of corporate social responsibility in public hospitals and the directors of communication at private hospitals. Findings: Although the private and public hospitals studied are in the same health-care industry and run similar operations, their organizational sustainability initiatives in the past, present and expected future differ. The scope of sustainability initiatives between private and public hospitals is different, compared through time. Who was and who is promoting, as well as who is going to promote sustainability initiatives, also differs between private and public hospitals. Research limitations/implications: One limitation of this study is that it was undertaken exclusively in Spanish organizations from one industry, but this is also a benefit, as it enables a comparison and contrast of the evolution between private and public hospitals. Future research could focus on the evolution of organizational sustainability initiatives in other industries and countries. Practical implications: The reported comparison of empirical findings between private and public hospitals, as well as the subsequent discussion contrasting these findings, yields various managerial implications in terms of the scope and promotor of sustainable actions. Originality/value: This study differs from previous ones by exploring the evolutionary details of the organizational sustainability initiatives through time in both private and public hospitals. This study also makes a contribution by revealing common denominators and differentiators between private and public hospitals that operate in the same health-care industry.